Effect of premature luteinizing hormone surge on pregnancy outcomes in intracytoplasmic sperm injection or in vitro fertilization cycles - Aldarsooni, Maram; Alfarah, Mohammad; Albohammod, Fatimah; Al-Jaroudi, Dania (Frontiers in Medicine, 2025)
Background A premature surge in luteinizing hormone (LH) during ovarian stimulation cycles between 12 and 25% has been commonly reported. However, there is still a lack of consensus on whether premature LH surge affects pregnancy outcomes. Objective This study aimed to evaluate the effect of premature LH surge on pregnancy rates in women with and without premature LH surge during intracytoplasmic sperm injection or stimulation of in vitro fertilization cycles at a tertiary hospital in Riyadh, Saudi Arabia. Materials and methods A cross-sectional study was conducted. Information related to 771 women who had IVF/ICSI cycles between January 2022 and December 2022 was reviewed. Patients were divided into two groups based on premature LH surge. Results There was no significant difference in patients’ characteristics. The live birth rates were significantly higher in women without premature LH surge than in women with LH surge (12.9% vs. 5.6%) (p = 0.010). With regard to the number of oocytes collected, M2, and fertilization rate, these were significantly higher in women without premature LH surge, with p-values of 0.001, 0.002, and 0.004, respectively. Conclusion The study demonstrates significantly higher live birth rates in women without premature LH surge.